India's New Education Policy 2020: Its Implications, Challenges and Strategies for AI Revolution in Education System - Saxena, Yogesh Kumar; Agarwal, Himanshu (Journal of Commerce and Trade, 2022)
India's New Education Policy (NEP) 2020 is a transformative framework that aims to reshape the country's education system. This analytical study critically examines the key features, implications, and challenges associated with the implementation and success of NEP 2020. It explores the potential impact of the policy on access to education, curriculum reforms, teacher training, assessment practices, technoinnovation in education, AI revolution in education and governance structures. The study highlights the opportunities offered by NEP 2020 and raises important considerations for effective implementation and addressing potential hurdles. The study explores the various aspects of the policy, including universalization of education, curriculum reforms, teacher training, assessment practices and governance structures. It examines its potential challenges viz. capacity building, teacher training, community engagement, monitoring and evaluation and infrastructure development for upcoming AI technology. The study aims to propose strategies and recommendations for the success of NEP 2020 in the present technology driven era. Thus, the study seeks to provide a comprehensive analysis of India's New Education Policy 2020, its implications, challenges and potential strategies for AI revolution in Education System. Quality education is the dire need of Indian youth to ensure their future in the current rapidly transforming socioeconomic- techno-innovative environment of the country. Classification-JEL: I24, I28, O31